Immunohistochemical Fiber Type Profile in the Human Vocal Muscle - López,María José (Sociedad Chilena de Anatomía, 2011)
The vocal muscle is a striated muscle with important functions in the emission of laryngeal sound and physiology of the voice. Therefore the knowledge of its constitution is the basis for the prevention and management of voice disorders. We used 10 samples from the middle third of vocal muscles obtained from autopsies of 6 male and 4 female subjects aged between 36 and 71 years. The samples were analyzed with BA-F8 monoclonal antibody to slow type I fibers, and antimyosin HC monoclonal antibody and antimyosin fast clone MY-32 antibody for types IIA, IIB, IIX, and neonatal fibers. We determined the distribution of the muscle fiber types and morphometric characteristics, evaluating the differences by sex and age group. The human vocal muscle presented a heterogeneous formation with a predominance of type II fibers at 51.99%, while type I fibers reached 48.01%; this difference was significant (p <0.05). Comparing fiber subtypes IIA and IIX, there is a slight predominance of type IIX fibers, although this is not statistically significant (p>0.05). In conclusion, the human vocal muscle the fibers were predominantly type II fast.